A fusion prognostics-based qualification test methodology for microelectronic products. (August 2016) - Pecht, Michael; Shibutani, Tadahiro; Kang, Myeongsu; Hodkiewicz, Melinda; Cripps, Edward
Abstract: The global market for microelectronic products is projected to reach US$2.4 trillion per year by 2020. This growth has led to intense competition between manufacturers to minimize the time-to-market for their products. Unfortunately, however, qualification testing, which is time-consuming and resource-intensive, is a major bottleneck for the quick release of microelectronic products to the market. Hence, for both researchers and engineers considering the time with reliability issues during qualification testing, this paper provides a review of conventional methodologies in qualification testing and presents a fusion prognostics-based qualification test methodology that combines the advantages of physics-of-failure and data-driven methods.